Dynamic Modeling, Simulation, And Control Of Switched Reluctance Motor Drive Based On Matlab/Simulink Environment - Rajandran, R.Vejian (2007)
This thesis focuses on the modeling and simulation of a switched reluctance motor (SRM) drive in a MATLAB/SIMULINK environment. With the physical SRM drive setup, 2.3 kW, 200 V, 8/6 SRM, the flux linkage and torque characteristics of the SRM were measured in the laboratory.